(3GbJWGa GdCRGgQ hGdJbGW GdLhGgQs - (3CMeO Hf jhSa Hf eGdc GdQYjfj GdZQfGWj GdCfOdSj, CHh LYaQ , J (B779 (3g` s
(3ChdgG (B:s
(3jbhd cGJHg CMeO Hf jhSa fMeO Gddg NGdb GdCaYGd CeG HYO CSJNQL GdOQQ ef CUOGagG , hCLeY GdahGFO Ydi CNJdGa CUfGagG aQCjJ Cf GdYde CTQa eG YfjJ Hg CcGHQ Gdedhc s
(3BNQgG (B:s
(3agPG BNQ eG GSJMVQJg jO GdGSJYLGd aEf dZI GdYQH HMQ dGjecf MUQg aef hLO MSfi adjYJQa , hef hLO ZjQ Pdc adjba hGdMeOddg ChdkG hBNQkG s
(3HgG fXGe GdJYbjHIs
(3cJGH ai aYd jaJM GdYjfs
(3hGdeVGQY efg HGdVe hGdcSQs
(3eY GNJdGa GdeYfi hGJaGbg eQJH Ydi MQha GdeYLe s
(3dYdg HNW GdeUfa s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs